Differentiating Atypical Hemangiomas and Metastatic Vertebral Lesions: The Role of T1-Weighted Dynamic Contrast-Enhanced MRI - Morales, K.A.; Arevalo-Perez, J.; Peck, K.K.; Holodny, A.I.; Lis, E.; Karimi, S. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Vertebral hemangiomas are benign vascular lesions that are almost always incidentally found in the spine. Their classic typical hyperintense appearance on T1- and T2-weighted MR images is diagnostic. Unfortunately, not all hemangiomas have the typical appearance, and they can mimic metastases on routine MR imaging. These are generally referred to as atypical hemangiomas and can result in misdiagnosis and ultimately additional imaging, biopsy, and unnecessary costs. Our objective was to assess the utility of dynamic contrast-enhanced MR imaging perfusion in distinguishing vertebral atypical hemangiomas and malignant vertebral metastases. We hypothesized that permeability and vascular density will be increased in metastases compared with atypical hemangiomas.MATERIALS AND METHODS: Consecutive patients from 2011 to 2015 with confirmed diagnoses of atypical hemangiomas and spinal metastases from breast and lung carcinomas with available dynamic contrast-enhanced MR imaging were analyzed. Time-intensity curves were qualitatively compared among the groups. Perfusion parameters, plasma volume, and permeability constant were quantified using an extended Tofts 2-compartment pharmacokinetic model. Statistical significance was tested using the Mann-Whitney U test.RESULTS: Qualitative inspection of dynamic contrast-enhanced MR imaging time-intensity curves demonstrated differences in signal intensity and morphology between metastases and atypical hemangiomas. Quantitative analysis of plasma volume and permeability constant perfusion parameters showed significantly higher values in metastatic lesions compared with atypical hemangiomas (P < .001).CONCLUSIONS: Our data demonstrate that plasma volume and permeability constant perfusion parameters and qualitative inspection of contrast-enhancement curves can be used to differentiate atypical hemangiomas from vertebral metastatic lesions. This work highlights the benefits of adding perfusion maps to conventional sequences to improve diagnostic accuracy.DCEdynamic contrast-enhancedKtranspermeability constantVHvertebral hemangiomaVpplasma volume